Potensi Ketersediaan Lahan Jagung untuk Mendukung Pasokan Biomassa Tongkol Jagung Berkelanjutan ke Pabrik CBG di Kabupaten Lombok Barat - Muflih, Rizaldi; Widiatmaka; Firmansyah, Irman; Aminah, Mimin (Jurnal Ilmu Tanah dan Lingkungan, 2025)
Land availability is crucial and determines the supply of corn cobs through sustainable corn cultivation to ensure the continuous production of compressed biogas (CBG). This study aims to assess the potential land for corn cultivation and the sustainability value of the corn cob supply for the CBG plant. The methods used in this study include overlaying land cover maps, spatial planning maps, and forest area maps, as well as conducting a Multiaspect Sustainability Analysis (MSA) to evaluate its sustainability level. The overlay results indicate that the potential additional land for corn cultivation in West Lombok Regency is 14,297 hectares. Meanwhile, the sustainability analysis reveals that the ecological aspect falls into the moderately sustainable category with a score of >50, namely 66.67. The social aspect has a sustainability score of 60, while the technology and infrastructure aspect scores 75, and the legal and institutional aspect also scores 66.67. The economic aspect is classified as less sustainable, with a score of <50, specifically 43.75. Overall, the sustainability status of the corn cob supply is categorized as moderately sustainable, with a score of 62.42.